The impact of independent campus learning program (MBKM) through matching fund program for lecturers, students and partners in Minggirsari Village, Blitar - Maduwinarti, Ayun; Ariyanto, Eko April; Narulita, Luvia Friska; Haque, Sayidah Auli'ul; Farhanindya, Hikmah Husniyah (Technium Social Sciences Journal, 2022)
One of the activities in the implementation of the Independent Campus Learning Program (MBKM) has been implemented through the Matching Fund program which was held in Minggirsari Village, Blitar. This activity has succeeded in establishing the Creative Economy and Tourism Research Center. The potential of Minggirsari village is divided into 17 sub-sectors based on creative economy sub sector, namely game development, architecture, interior design, music, fine arts, product design, fashion, culinary, film-animation-video, photography, visual communication design, TV-radio, crafts, advertising, performing arts, publishing and applications. The synergy between intellectuals, business, and government is the main actor driving the birth of creativity, ideas, science and technology that are vital for the growth of creative industries in Indonesia. Based on the existing potential, this activity provides the widest possible learning space to improve students' ability in creative thinking and critical thinking to enter the business world. In addition, this activity is also a forum for lecturers to develop research results on the creative economy. This activity also facilitates village residents to get provisions in developing their potential to help build Minggirsari village into a creative economy village. For this reason, this research is expected to be able to measure the impact resulting from learning activities that have been carried out through the matching fund program for lecturers, students and partners. This research uses a quantitative approach with a survey method. Data analysis in this study used descriptive data analysis methods.